2014
DOI: 10.1017/s0043933914000646
|View full text |Cite
|
Sign up to set email alerts
|

Significance of scavenging chicken production in the rural community of Africa for enhanced food security

Abstract: their eggs and meat suggests that these genetic resources are promising options for food security in the rural communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…However, in Danki birds of India, Vijh et al (2005) documented a mortality rate of around 20-30 percent during first 2 months of age, similar to the result of present study. Similar to the results of the present study, preponderance of Newcastle disease (Olwande et al, 2010;Melesse, 2014) and high disease occurrence in dry summer seasons (Sonaiya and Swan, 2004) in village chicken have already been established. The study revealed that altogether there is 69.38 percent depletion from day-old to 72 weeks of age in village chicken much higher than that of intensively reared commercial layers (Farooq et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, in Danki birds of India, Vijh et al (2005) documented a mortality rate of around 20-30 percent during first 2 months of age, similar to the result of present study. Similar to the results of the present study, preponderance of Newcastle disease (Olwande et al, 2010;Melesse, 2014) and high disease occurrence in dry summer seasons (Sonaiya and Swan, 2004) in village chicken have already been established. The study revealed that altogether there is 69.38 percent depletion from day-old to 72 weeks of age in village chicken much higher than that of intensively reared commercial layers (Farooq et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Scavenging chicken production is a profitable enterprise that contributes to poverty reduction especially among the resource challenged rural communities in most parts of the world (Melesse, 2014). In a large numbers of developing countries in Africa and Asia, indigenous birds constitute up to 80 percent of the standing poultry population (Pym, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Indigenous chicken are widely distributed in the rural areas of tropical and sub-tropical countries (Ajayi 2010). The birds play a key role for the poor farmers and the underprivileged within the rural setting as regards subsidiary income, provision of chicken meat and eggs (Padhi 2016) and food security (Melesse 2014). In spite of this, smallholder poultry subsector in sub-Saharan Africa is beset with myriad of problems among which are poor nutrition, limited technical know-how, vagaries of climatic factors, slow-growing, low meat yield, small size/number of eggs, low input, and high mortality (Yakubu, 2010;Ayanwale et al 2015;Dessie, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Local populations of chicken that are genotypically, phenotypically, and geographically distinct from each other hold nutritional, economic and cultural importance for smallholder farmers. Although their productivity is much lower than commercial lines, they are posited to be adapted to local climatic and pathogenic insults 2,3 . Globally, almost 1600 distinct regional breeds of chicken are recognised 4 and the utilisation of this diversity through the identification and validation of genetic variants for increased resistance to disease and heat stress will benefit both commercial and small holder farmers 5 .…”
Section: Mainmentioning
confidence: 99%